A Systematic Review of the Literature and Perspectives on the Role of Biomarkers in the Management of Malnutrition After Allogeneic Hematopoietic Stem Cell Transplantation - Morello, Enrico; Guarinoni, Milena Giovanna; Arena, Francesco; Andreoli, Marco; Bernardi, Simona; Malagola, Michele; Turra, Alessandro; Polverelli, Nicola; Russo, Domenico (Frontiers in Immunology, 2021)
Malnutrition is a common problem after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and could impair immune function. Immune dysfunction after allo-HSCT may be linked with infections, GVHD and relapse and negatively affect the outcome. Aim of this review was to identify malnutrition biomarkers, potentially useful for immune-system monitoring, in the setting of allo-HSCT. After a systematic search, no satisfying biomarker was found, except for citrulline. Citrulline could be useful in monitoring gastrointestinal function after allo-HSCT and its role in the complex relationship with immune-system function ought to be better explored. A multi-omics approach, including biomarkers and PRO (patient reported outcomes) is, in our opinion, the optimal way to study the relationship between malnutrition and transplant outcomes.